Pengaruh Cita Rasa, Kualitas Pelayanan, Harga dan Lokasi Terhadap Keputusan Pembelian pada Martabak Bangka Indah Rantau Prapat - Tiara Ilhani Siregar; Rizky Syahputra; Bhakti Helvi Rambe (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the effect of taste, service quality, price, and location on the purchase decision at Martabak Bangka Indah in Rantau Prapat. This research uses a descriptive study with a quantitative approach. Data were collected through the distribution of questionnaires to 100 respondents who are customers of Martabak Bangka Indah. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of this study show that the taste variable (X1) has a positive and significant effect on purchase decision, the service quality variable (X2) has a positive and significant effect on purchase decision, the price variable (X3) has a positive and significant effect on purchase decision, and the location variable (X4) has a positive and significant effect on purchase decision. Therefore, it can be concluded that the taste, service quality, price, and location variables all have an impact on the purchase decision.